Spices and Hypertension: An Insight for Researchers - Nair, Kavyanjana R.; V.S, Arya; S.K., Kanthlal; P., Uma D. (Current Nutrition & Food Science, 2022)
Hypertension is a global public health concern since it can lead to complications like stroke, heart disease, and kidney failure. These complications can add to a disability, increase healthcare costs, and can even result in mortality. In spite of the availability of a large number of anti-hypertensive drugs, the control of blood pressure is suboptimal in many patients. Spices have been used as flavouring agents and in treating diseases in folk medicine since they are considered to be rich sources of phytochemicals, especially polyphenols. Hence, during recent years, there has been renewed interest among researchers in exploring natural sources, especially spices, in an attempt to find cheaper alternatives with fewer side effects. Our aim is to review the relevant preclinical and clinical studies focused on the potential use of spices in the management of hypertension. Studies conducted on the most common spices, such as celery, cinnamon, cardamom, garlic, ginger, saffron, and turmeric, have been elaborated in this review. These spices may lower blood pressure via several possible mechanisms, including antioxidant effect, increase in nitric oxide production, reduction in calcium ion concentration, modulation of the renin-angiotensin pathway, etc.
Keywords: turmeric